First record of Piscinoodinium pillulare (Dinoglagellida) infestation in juveniles of Colossoma macropomum (Characiformes: Serrasalmidae) in semi-intensive fish farming in Loreto, Peru - Arbildo Ortiz, Humberto (2020)
The aim of this study was to describe a case of Piscinoodinium pillulare infestation and mortality in juveniles of Colossoma macropomum. In March 2019, 21 juvenile specimens of a semi-intensive fish farm were collected in the Maynas area, Loreto (Peru). Parasitological analysis of the external parts of the fish was performed and the presence of P. pillulare located on the skin, fins, gills, and nostrils was observed. Furthermore, a 30% mortality was recorded (1500 out of 5000 seeded). The non-disinfection of the pond, the inadequate control in the feeding, and the proliferation of Oreochromis niloticus (tilapia) in the culture were the causes of the proliferation of P. pillulare. This is the first reported case of P. pillulare infestation in juveniles of C. macropomum grown in the Peruvian Amazon.